An Improved Proportional Integral Estimator of the Stator Resistance for a Direct Torque Controlled Induction Motor, ISSN 1934-8975 - Benlarbi Keltoum; Mokrani Lakhdar; Mokhnache Leila (Journal of Energy and Power Engineering, 2013)
In this paper, an improved PI (proportional integral) stator resistance estimation for a DTC (direct torque controlled) induction motor is proposed. This estimation method is based on an on-line stator resistance correction regarding the variations of the stator current estimation error. In fact, the input variable of the PI estimator is the stator current estimation error. The main idea is to tune accurately the stator resistance value relatively to the evolution of the stator current estimation error gradient to avoid the drive instability and …